Numerical simulation of cloud- clear air interfacial mixing - Andrejczuk, M; Grabowski, W; Malinowski, S; Smolarkiewicz, P (2004)
This paper discusses results from a series of direct numerical simulations of the microscale cloud-clear air mixing, set forth in the idealized scenario of decaying moist turbulence. In the moist case, kinetic energy of microscale motions comes not only from the classical downscale energy cascade, but it can also be generated internally due to the evaporation of cloud droplets. Three sets of numerical simulations are performed for three intensities of initial large-scale eddies. In each set, a control dry simulation is performed, as well as two moist simulations applying either bulk or detailed representation of cloud microphysics. Model results suggest that, as far as the evolutions of enstrophy and turbulent kinetic energy are concerned, the most significant impact of moist processes occurs at the low intensity of initial large-scale eddies (the input turbulent kinetic energy of 2 X 10-4 m2 s-2 resulting in the maximum eddy dissipation rate of 5 X 10-4 m2 s-3). In such a case, mixing and homogenization are dominated by the kinetic energy generated as a result of evaporation of cloud water and its impact on the microscale buoyancy. Detailed microphysics, which explicitly treat the size dependence of cloud droplet sedimentation and evaporation, appear to have a comparatively small effect, although this result might be an artifact of a coarse grid resolution used in the simulations. High anisotropy, also observed in laboratory experiments with mixing, between cloudy and cloud-free air, prevails even at the high intensity of initial large-scale eddies (the input turbulent kinetic energy of 2 X 10-2 m2 s-2, the maximum eddy dissipation rate of 7 × 10-3 m2 s-3), despite the fact that mixing and homogenization proceed in a similar manner in moist and dry simulations. Impact on cloud microphysics is also quantified. Cloud droplet spectra at the end of simulations correspond to neither the extremely inhomogeneous nor homogeneous mixing scenarios-the two asymptotic limits where, respectively, either the cloud droplet size or the number of cloud droplets remain constant. The shift from low to high intensity of initial large-scale eddies shifts the mixing scenario toward the homogeneous case, corroborating the classical argument based on scale analysis. © 2004 American Meteorological Society.